(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
Small businesses firms remain the most competitive industry, and they require both business and strategic planning in order to remain competitive. Small enterprises, which include agriculture and rural businesses, have made significant contributions to the economy’s growth, mostly through the creation of jobs. There have been a lot of failures and a lot of bad shows. Within the first few years, many small enterprises face the prospect of failure. Many small businesses thrive when they launch, but only a handful thrive for the rest of their lives and evolve into big businesses. It has been established that lack of both business planning and strategic planning thwart them from achieving their potential. This study therefore attempts to figure out the relationship between business planning and strategic planning on business success. Based on the study literature, it was established that the most successful businesses use strategic planning, and there is a high failure rate for those who do not. The recommendation is that the business owners should be trained in the skills of both business and strategic planning.